Carriers of haemophilia a and B – a 5 year retrospective audit of management in pregnancy in the setting of a tertiary referral clinic. (18th April 2012) - Carney, S-K; Kemp, S; Hay, C; Nash, M; Hay, E; Hobson, M; Byrd, L
Abstract : Haemophilia A and B are both X linked recessive conditions with an incidence of 1 in 5000 and 1 in 30, 000 males respectively. Carriers have a 50% chance of passing on the gene defect to their offspring with 50% chance of having a carrier daughter, and 50% chance of having an affected son. The Joint Obstetric Haematology Clinic in Manchester provides tertiary level care for women across the North West. A 5 year retrospective audit of the management of all women (20) identified as being haemophilia carriers was undertaken. All women accepted early fetal sexing. Five women were carrying female infants and were transferred back to their base hospital, or own consultant. The other 15 cases had delivery care plans written at 36 weeks gestation. All included advice concerning regional anaesthesia, judicious use of fetal blood sampling (FBS) and non rotational forceps, and no ventouse. Cord bloods for neonatal factor levels and oral vitamin K for babies affected was also advised. Advice re post partum haemorrhage (PPH) was included in 5 (28%) plans. Of the 16 women delivered at St Mary's all presented in spontaneous labour; 12 (75%) underwent normal vaginal deliveries (average blood loss 240mls), 1 mid-cavity forceps and 3 Emergency LSCS (all related to abnormal CTGs with no FBS) (average blood loss 23000mls). Of the 15 male babies 3 were (20%) affected; there was no neonatal morbidity. Whilst the outcomes were good – there is a general reluctance to undertake FBS. The role of late amniocentesis is being explored.